In-air hearing in Hawaiian monk seals: implications for understanding the auditory biology of Monachinae seals - Ruscher, Brandi; Sills, Jillian M.; Richter, Beau P.; Reichmuth, Colleen (Journal of Comparative Physiology A, 2021)
Abstract The auditory biology of Monachinae seals is poorly understood. Limited audiometric data and certain anatomical features suggest that these seals may have reduced sensitivity to airborne sounds compared to related species. Here, we describe the in-air hearing abilities of a Hawaiian monk seal ( Neomonachus schauinslandi ) trained to participate in a psychophysical paradigm. We report absolute (unmasked) thresholds for narrowband signals measured in quiet conditions across the range of hearing and masked thresholds measured in the presence of octave-band noise at two frequencies. The behavioral audiogram indicates a functional hearing range from 0.1 to 33 kHz and poor sensitivity, with detection thresholds above 40 dB re 20 µPa. Critical ratio measurements are elevated compared to those of other seals. The apparently reduced terrestrial hearing ability of this individual—considered with available auditory data for a northern elephant seal ( Mirounga angustirostris )—suggests that hearing in Monachinae seals differs from that of the highly sensitive Phocinae seals. Exploration of phylogenetic relationships and anatomical traits support this claim. This work advances understanding of the evolution of hearing in amphibious marine mammals and provides updated information that can be used for management and conservation of endangered Hawaiian monk seals.